2015
DOI: 10.1177/1358863x15591201
|View full text |Cite
|
Sign up to set email alerts
|

Soluble vascular endothelial-cadherin and auto-antibodies to human vascular endothelial-cadherin in human diseases: Two new biomarkers of endothelial dysfunction

Abstract: Vascular endothelial-cadherin is the most important transmembrane component of endothelial adherens junctions, exclusively expressed by endothelial cells in all types of vessels. Targeting either the extracellular domain or the cytoplasmic tail deleteriously affects the junctional strength and leads to vascular permeability. Recently, cytokineinduced phosphorylation of the vascular endothelial-cadherin cytoplasmic domain was reported to trigger cleavage of its extracellular domain, producing the soluble form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…In addition, the cytoplasmic tail of VE-cadherin links to the cytoskeleton by binding directly and indirectly with various catenins, including β-catenin [8,15]. Targeting either the extracellular domain or the cytoplasmic tail deleteriously affects the junctional strength and leads to vascular permeability [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the cytoplasmic tail of VE-cadherin links to the cytoskeleton by binding directly and indirectly with various catenins, including β-catenin [8,15]. Targeting either the extracellular domain or the cytoplasmic tail deleteriously affects the junctional strength and leads to vascular permeability [16].…”
Section: Introductionmentioning
confidence: 99%
“…Cadherins are known to play an important role in vascular cell function and angiogenesis, while Wnt signaling has been implicated to promote vascular remodeling and even cardiovascular regeneration. 36,37 Using three different functional assays we confirmed that editing-induced targetome changes result in angiogenesis-associated functional changes. We assessed the effect of WT-microRNAs and ED-microRNAs on in vitro scratch-wound healing and tube formation, and ex vivo neovessel sprouting, and consistently found that ED-microRNAs had increased pro-angiogenic properties compared to the WT-microRNAs.…”
Section: Discussionmentioning
confidence: 59%
“…We have previously shown that TLR2 activation by LTA from Staphylococcus aureus has deleterious effects on endothelial cell adhesion and increases permeability ( 19 ). Cadherin is critical in maintaining the integrity of intercellular junctions creating a restrictive endothelial barrier ( 20 ). Soluble vascular endothelial cadherin has been shown to be a prognostic marker in inflammatory disease states ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cadherin is critical in maintaining the integrity of intercellular junctions creating a restrictive endothelial barrier ( 20 ). Soluble vascular endothelial cadherin has been shown to be a prognostic marker in inflammatory disease states ( 20 , 21 ). We found the mean of measured plasma markers of inflammation (IL-6, hepcidin) and endothelial barrier dysfunction (sVE cadherin) to be much higher than values reported for healthy subjects ( 14 , 15 , 22 ).…”
Section: Discussionmentioning
confidence: 99%